BILATERALLY ASYMMETRICAL BECKER'S NEVUS - Zainab, Zarnab; Malik, Naveed Akhtar; Obaid, Shanza; Mumtaz, Maimoona; Aftab, Kanza; Malik, Saqib; Pervaiz, Alia; Syed, Zainab (Journal of Ayub Medical College Abbottabad, 2021)
Becker's nevus is a main epidermal hypermelanotic condition that usually presents in adolescence, though childhood cases are seen less commonly. Congenital cases have been rarely reported. Nevus is usually unilateral having increased pigmentation and is characterized by hypertrichosis. It usually presents as a patch on back, proximal upper extremities, arms and upper trunk. Becker's Nevus presenting as bilateral asymmetrical patch is rare. A case of 23 year's old male with bilateral hyperpigmentad patch over the back has been reported. The histological exams established the clinical hypothesis of Becker's Nevus.